2009
DOI: 10.1148/radiol.2522081882
|View full text |Cite
|
Sign up to set email alerts
|

Association between MucoidPseudomonasInfection and Bronchiectasis in Children with Cystic Fibrosis

Abstract: Purpose:To correlate the severity of bronchiectasis in children with cystic fibrosis with clinical and microbiologic variables in order to clarify risk factors for the development of irreversible lung disease. Materials and Methods:After institutional review board approval and parental informed consents were obtained, a HIPAA-compliant longitudinal epidemiologic evaluation was performed in patients with cystic fibrosis who were enrolled in the Wisconsin trial of newborn screening from 1985 to 2009. Thinsection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
41
1
4

Year Published

2010
2010
2023
2023

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 59 publications
(52 citation statements)
references
References 51 publications
6
41
1
4
Order By: Relevance
“…(12) A study involving 82 patients with CF and evaluating 12 risk factors for developing irreversible lesions (such as bronchiectasis) found that only colonization with mucoid P. aeruginosa was significantly correlated with the presence of bronchiectasis. (19) The results of the present study are in agreement with those of the studies cited above. All of the patients who were chronically colonized with P. aeruginosa presented with the mucoid phenotype, and HRCT revealed a significantly higher prevalence of bronchiectasis in those patients.…”
Section: Discussionsupporting
confidence: 93%
“…(12) A study involving 82 patients with CF and evaluating 12 risk factors for developing irreversible lesions (such as bronchiectasis) found that only colonization with mucoid P. aeruginosa was significantly correlated with the presence of bronchiectasis. (19) The results of the present study are in agreement with those of the studies cited above. All of the patients who were chronically colonized with P. aeruginosa presented with the mucoid phenotype, and HRCT revealed a significantly higher prevalence of bronchiectasis in those patients.…”
Section: Discussionsupporting
confidence: 93%
“…One case was also combined with patchy ground-glass opacities. Results of previous studies (Brody, 2008;Farrell et al, 2009) and the present study suggest that bronchiectasis is the first indicator of the final pathological stage of children's ILD and is an unrecoverable image manifestation.…”
Section: Bronchiectasissupporting
confidence: 45%
“…Interpretation of these investigations is complicated by the fact that some experts feel that emergence of the mucoid phenotype coincides with the transition from the intermittent to the chronic phase of infection (293,452,464) whereas others feel that chronic infection usually precedes the emergence of mucoid P. aeruginosa (30). Regardless of these distinctions, it is clear that chronic infection with mucoid P. aeruginosa is associated with poorer outcomes in CF patients (184,250,269). Pedersen and colleagues performed spirometry on 73 patients with CF over a period of 13 years (453).…”
Section: Pseudomonas Aeruginosamentioning
confidence: 99%